A CASE REPORT: POSTOPERATIVE EPIDURAL HEMATOMA AFTER MENINGIOMA RESECTION - Anastasya Chanita Putri Maharani; Feda Anisah Makkiyah (The SDGS Forum Communication, 2026)
Postoperative Epidural Hematoma (PEDH) is a rare but potentially life-threatening complication following craniotomy for intracranial tumor resection, particularly in elderly patients. The incidence of postoperative epidural hematoma is estimated to be approximately 1-2% of intracranial surgeries, and its development is often attributed to rapid reductions in intracranial pressure, excessive cerebrospinal fluid drainage, or coagulation abnormalities. This report presents a 71-year-old female who developed PEDH following craniotomy for meningioma. The patient initially showed stable postoperative recovery but experienced sudden neurological deterioration, prompting an urgent CT scan that revealed an epidural hematoma. Immediate surgical intervention was performed to evacuate the hematoma, leading to gradual neurological improvement. This case highlights the importance of early detection, rapid intervention, and careful perioperative management to optimize outcomes in patients with PEDH